PENGARUH UMUR, JENIS KELAMIN, JAM KERJA, STATUS PEKERJAAN DAN PENDIDIKAN TERHADAP PENDAPATAN TENAGA KERJA DI KOTA PADANG - Ghiana Desanti; Ariusni Ariusni (Universitas Negeri Padang, 2021)
This study aims to determine and analyze how the influence of age, gender, working hours, employment status and education on the income of workers in the city of Padang. The types and sources of data in this study are from the National Labor Force Survey (SAKERNAS in 2019. In this study, multiple regression analysis was used to see the effect of the independent variables on the dependent variable with the number of samples used as many as 912 workers. The results of this study indicate that age has a positive and significant effect on labor incomein Padang City, gender has a positive and significant effect on labor income in Padang City, working hours have a positive and significant effect on labor income in Padang City, employment status has a positive effect. and significant to the income of workers in the city of Padang, education also affects the income of workers in the city of Padang.